Transformation of Traditional Learning Models in Elementary Schools in Lampung Province: An Adaptation Approach - Arrasyid, Abi Krisna; Herpratiwi, Herpratiwi; Sinaga, Risma Margaretha; Fitri, Dina Martha (Jurnal Pendidikan Progresif, 2025)
Transformation of Traditional Learning Models in Elementary Schools in Lampung Province: An Adaptation Approach. Objective: This study aims to explore the transformation of traditional learning models in elementary schools in Lampung Province in response to the emerging challenges and opportunities of the digital era. The main focus is to examine how the adaptation of instructional approaches, particularly in methods, media, and teacher roles, can improve the quality of basic education through the integration of information and communication technology (ICT). This transformation is viewed as essential in meeting the educational demands of the 21st century. Methods: This research employs a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The study participants include teachers, principals, and students from several elementary schools in Lampung Province that have initiated the implementation of digital learning models. Thematic analysis was employed to identify patterns of adaptation, challenges in implementation, and strategies developed to address these changes. Findings: The study reveals that learning transformation involves not only the use of technology but also significant shifts in the teacher's role as a facilitator, more participatory teaching strategies, and dynamic patterns of interaction. Key challenges include limited ICT infrastructure, human resource readiness, and resistance to school culture change. However, there are significant opportunities through teacher training, digital curriculum development, and supportive education policies. The two most important findings are: first, teachers successfully modified traditional teaching into project-based and collaborative learning supported by ICT; second, students showed increased engagement and learning motivation in interactive digital environments. Conclusion: The transformation of learning models in elementary schools is a complex process that requires fundamental changes in how knowledge is constructed, shared, and applied. Collaborative strategies among educational stakeholders, sufficient technological support, and capacity-building for teachers are essential to establishing an adaptive, inclusive, and sustainable learning ecosystem. This study makes a conceptual contribution by demonstrating that teacher agency in resource-constrained settings can bridge the gap between global constructivist pedagogical ideals and local sociocultural realities, resulting in a unique and contextually grounded hybrid learning model. Keywords: learning transformation, digital era, educational technology, education quality, teacher roles.